Inszenierung - Pauls, Karina; Nafe, Nadja (Lexikon der Kunstpädagogik)

Installation - Pauls, Karina (Lexikon der Kunstpädagogik)

Schnittstelle Kunstunterricht: Körper - Raum – Skulptur

Materialität - Pauls, Karina (Lexikon der Kunstpädagogik)

Studio Thinking - Pauls, Karina (Lexikon der Kunstpädagogik)

Lernort Schule - Pauls, Karina (Lexikon der Kunstpädagogik)

Relief - Pauls, Karina (Lexikon der Kunstpädagogik)

Werken - Pauls, Karina (Lexikon der Kunstpädagogik)

Rezension zu Kunibert Bering: Kunstunterricht und Bildung. Kulturelles Gedächtnis, Globalität, innovative Perspektiven - Pauls, Karina (Kunst+Unterricht 459/460)

Lexikon der Kunstpädagogik

Stable bipolarons in open quantum systems - Moroder, Mattia; Grundner, Martin; Damanet, François; Schollwöck, Ulrich; Mardazad, Sam; Flannigan, Stuart; Köhler, Thomas; Paeckel, Sebastian (Physical Review B 107, 214310 (2023))
Recent advances in numerical methods significantly pushed forward the understanding of electrons coupled to quantized lattice vibrations. At this stage, it becomes increasingly important to also account for the effects of physically inevitable environments. In particular, we study the transport properties of the Hubbard-Holstein Hamiltonian that models a large class of materials characterized by strong electron-phonon coupling, in contact with a dissipative environment. Even in the one-dimensional and isolated case, simulating the quantum dynamics of such a system with high accuracy is very challenging due to the infinite dimensionality of the phononic Hilbert spaces. For this reason, the effects of dissipation on the conductance properties of such systems have not been investigated systematically so far. We combine the non-Markovian hierarchy of pure states method and the Markovian quantum jumps method with the newly introduced projected purified density-matrix renormalization group, creating powerful tensor-network methods for dissipative quantum many-body systems. Investigating their numerical properties, we find a significant speedup up to a factor $\sim 30$ compared to conventional tensor-network techniques. We apply these methods to study dissipative quenches, aiming for an in-depth understanding of the formation, stability, and quasi-particle properties of bipolarons. Surprisingly, our results show that in the metallic phase dissipation localizes the bipolarons, which is reminiscent of an indirect quantum Zeno effect. However, the bipolaronic binding energy remains mainly unaffected, even in the presence of strong dissipation, exhibiting remarkable bipolaron stability. These findings shed light on the problem of designing real materials exhibiting phonon-mediated high-$T_C$ superconductivity.

Statistical analysis of initial state and final state response in heavy-ion collisions - Borghini, Nicolas; Borrell, Marc; Feld, Nina; Roch, Hendrik; Schlichting, Sören; Werthmann, Clemens (Phys. Rev. C 107 (2023) 034905)
We develop a general decomposition of an ensemble of initial density profiles in terms of an average state and a basis of modes that represent the event-by-event fluctuations of the initial state. The basis is determined such that the probability distributions of the amplitudes of different modes are uncorrelated. Based on this decomposition, we quantify the different types and probabilities of event-by-event fluctuations in Glauber and Saturation models and investigate how the various modes affect different characteristics of the initial state. We perform simulations of the dynamical evolution with KoMPoST and MUSIC to investigate the impact of the modes on final-state observables and their correlations.

Plant mitochondrial RNA editing factors can perform targeted C-to-U editing of nuclear transcripts in human cells - Lesch, Elena; Schilling, Maximilian T; Brenner, Sarah; Yang, Yingying; Gruss, Oliver J; Knoop, Volker; Schallenberg-Rüdinger, Mareike (Nucleic Acids Research)
Abstract RNA editing processes are strikingly different in animals and plants. Up to thousands of specific cytidines are converted into uridines in plant chloroplasts and mitochondria whereas up to millions of adenosines are converted into inosines in animal nucleo-cytosolic RNAs. It is unknown whether these two different RNA editing machineries are mutually incompatible. RNA-binding pentatricopeptide repeat (PPR) proteins are the key factors of plant organelle cytidine-to-uridine RNA editing. The complete absence of PPR mediated editing of cytosolic RNAs might be due to a yet unknown barrier that prevents its activity in the cytosol. Here, we transferred two plant mitochondrial PPR-type editing factors into human cell lines to explore whether they could operate in the nucleo-cytosolic environment. PPR56 and PPR65 not only faithfully edited their native, co-transcribed targets but also different sets of off-targets in the human background transcriptome. More than 900 of such off-targets with editing efficiencies up to 91%, largely explained by known PPR-RNA binding properties, were identified for PPR56. Engineering two crucial amino acid positions in its PPR array led to predictable shifts in target recognition. We conclude that plant PPR editing factors can operate in the entirely different genetic environment of the human nucleo-cytosol and can be intentionally re-engineered towards new targets.
Keywords: Genetics

Das Hubble-Teleskop: Mehr als 30 Jahre Beobachtung. - Hohmann, Sascha (Astronomie + Raumfahrt im Unterricht)

Comparison: Stochastics with a Focus on Probability Theory - Stoffels, Gero; Hohmann, Sascha (Comparison of Mathematics and Physics Education II. Examples of Interdisciplinary Teaching at School)

Comparison: Equations in Mathematics and Physics Education - Hohmann, Sascha; Pielsticker, Felicitas (Comparison of Mathematics and Physics Education II. Examples of Interdisciplinary Teaching at School)

Das Stellarium Gornergrat: Ein ferngesteuertes Observatorium für Bildungszwecke. - Gschwind, Stéphane; Hohmann, Sascha; Müller, Andreas; Riesen, Timm-Emanuel (Astronomie + Raumfahrt im Unterricht)

Wie die Wikinger das Nordmeer überqueren konnten - Hohmann, Sascha (Astronomie + Raumfahrt im Unterricht)

Wortkritik als Aufgabenfeld einer diversitätssensiblen Literaturdidaktik. Das Verfahren der Dechiffrierung als ein Weg fachintegrativer Verankerung von Diversitätssensibilität - Kißling, Magdalena (Diversitätsorientierte Deutschdidaktik: Theoretisch-konzeptionelle Fundierung und Perspektiven für empirisches Arbeiten. Band 4 SLLD (B))
Keywords: Diversität; Inklusion; Gender; Deutschdidaktik

‚Nofretete-Mädchen‘ als Aufstörende des Adipositas-Mythos. Interkulturelle Perspektive auf Adoleszenz am Beispiel von Stefanie Höflers Tanz der Tiefseequalle - Kißling, Magdalena (Adoleszenz und Alterität. Synergien aktueller Ansätze der interkulturellen Literaturwissenschaft und -didaktik)